A trivariate Bernoulli regression model. Issue 1 (1st January 2018) - Islam, M. Ataharul
Abstract: A trivariate Bernoulli regression model is proposed in this paper. There is extensive need for analysing repeated binary outcomes where correlated binary outcomes are obtained from repeated measures or longitudinal data. The proposed model is based on marginal and conditional probabilities as functions of covariates. The estimation and test procedures are shown. The tests include testing of hypotheses for first- and second-order associations among outcome variables. It is noteworthy that the test procedures for dependence in outcome variables can be demonstrated in terms of vectors of regression parameters for models on outcome variables. The proposed model can be extended for more than three correlated outcome variables conveniently.